Synthesis of porous carbon nanofiber with bamboo-like carbon nanofiber branches by one-step carbonization process - Yoo, Seung Hwa; Joh, Han-Ik; Lee, Sungho (ELSEVIER SCIENCE BV, 2017)
Porous carbon nanofibers (PCNFs) with CNF branches (PCNF/bCNF) were synthesized by a simple heat treatment method. Conventional methods to synthesize this unique structure usually follow a typical route, which consists of CNF preparation, catalyst deposition, and secondary CNF growth. In contrast, our method utilized a one-step carbonization process of polymer nanofibers, which were electrospun from a one-pot solution consisted of polyacrylonitrile, polystyrene (PS), and iron acetylacetonate. Various structures of PCNF/CNF were synthesized by changing the solution composition and molecular weight of PS. It was verified that the content and molecular weight of PS were critical for the growth of catalyst particles and subsequent growth of CNF branches. The morphology, phase of catalyst, and carbon structure of PCNF/bCNF were analyzed at different temperature steps during carbonization. It was found that pores were generated by the evaporation of PS and the catalyst particles were formed on the surface of PCNF at 700 degrees C. The gases originated from the evaporation of PS acted as a carbon source for the growth of CNF branches that started at 900 degrees C. Finally, when the carbonization process was finished at 1200 degrees C, uniform and abundant CNF branches were formed on the surface of PCNF. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: STRUCTURED CARBON; CATALYTIC GROWTH; FIBER; NANOPARTICLES; NANOTUBES